Molecular-cytogenetic criteria of prognosis of plasma cell myeloma course - Мішаріна, Ж. А.; Мінченко, Ж. М.; Курченко, А. І.; Любарець, Т. Ф.; Дмитренко, О. О.; Бебешко, В. Г. (Problems of Environmental Biotechnology, 2017)
According to the results of the molecular-cytogenetic examination of patients with plasma cell myeloma (PCM) at different stages of therapy, chromosomal abnormalities were detected in almost 80 % of patients. Changes of chromosomes 3, 8, 11 and 13 were predominant, associated with the hyperdiploid type of chromosomal aberrations in the most of patients. IgH translocation with the involvement of chromosomes 4, 11 and 16 was detected in 15 % of patients. The obtained data indicate a significant association of the revealed chromosomal abnormalities with the risk of primary refractory to therapy and the occurrence of complications (range of Spеаrman coefficient from Ro Spеаrman = 0,33 to Ro Spеаrman = 0,5; p < 0,05), which makes it possible to consider them as prognostic criteria for the PCM course.